Limited Dissolved Phosphorus Runoff Losses from Layered Double Hydroxide and Struvite Fertilizers in a Rainfall Simulation Study. Issue 2 (1st March 2018) - Everaert, Maarten; da Silva, Rodrigo C.; Degryse, Fien; McLaughlin, Mike J.; Smolders, Erik
Abstract : The enrichment of P in surface waters has been linked to P runoff from agricultural fields amended with fertilizers. Novel slow‐release mineral fertilizers, such as struvite and P‐exchanged layered double hydroxides (LDHs), have received increasing attention for P recycling from waste streams, and these fertilizers may potentially reduce the risk of runoff losses. Here, a rainfall simulation experiment was performed to evaluate P runoff associated with the application of recycled slow‐release fertilizers relative to that of a soluble fertilizer. Monoammonium phosphate (MAP), struvite, and LDH granular fertilizers were broadcasted at equal total P doses on soil packed in trays (5% slope) and covered with perennial ryegrass ( Lolium perenne L.). Four rainfall simulation events of 30 min were performed at 1, 5, 15, and 30 d after the fertilizer application. Runoff water from the trays was collected, filtered, and analyzed for dissolved P. For the MAP treatment, P runoff losses were high in the first two rain events and leveled off in later rain events. In total, 42% of the applied P in the MAP treatment was lost due to runoff. In the slow‐release fertilizer treatments, P runoff losses were limited to 1.9 (struvite) and 2.4% (LDH) of the applied doses and were more similar over the different rain events. The use of these novel P fertilizer forms could be beneficial in areas with a high risk of surface water eutrophication and a history of intensive fertilization. Core Ideas: Granular struvite and LDH are known as slow‐release fertilizers (SRFs). For the first time, struvite and LDH were tested in a runoff experiment. 42% of P in the MAP treatment was lost as DP due to runoff. Struvite and LDH showed much lower loss (<3% of applied P) than MAP. Applying SRFs can be considered in areas and times with a high risk of eutrophication.